Ilusi Kemitraan dalam Wacana Ekonomi Berbagi - Hasan Labiqul Aqil (IAIN Salatiga, 2023)
The emergence of various digital platforms in the era of the internet technology revolution, in addition to giving birth to various new job types, also gives rise to a new term for workers, the term ‘mitra’ in the